2015
DOI: 10.1515/acph-2015-0020
|View full text |Cite
|
Sign up to set email alerts
|

Rational application of fructose-1,6-diphosphate: From the perspective of pharmacokinetics

Abstract: Fructose-1,6-diphosphate (FDP), a glycolytic metabolite, has been reported to protect susceptible organs during hypoxia or ischemia. However, there is paucity of human data on its pharmacokinetics a er being exogenously administered. In the current study, the preliminary pharmacokinetics of FDP given orally to humans was investigated, and no typical peak was observed in the serum drug-time curve. Then, the pharmacokinetic studies were performed following multiple doses of FDP in rats, and the Caco-2 monolayer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…The level stayed above the base line concentration up to 72h. For rats receiving 180 mg/kg FBP orally every 8 h for 7 consecutive days, FBP levels in plasma peaked at 182 μg/ml after 45 min [36]. To our knowledge, there is no report on the amount of FBP captured by lung after IP administration in mice, although reports can be found that it can prevent ischemic lung injury in rats [37].…”
Section: Discussionmentioning
confidence: 99%
“…The level stayed above the base line concentration up to 72h. For rats receiving 180 mg/kg FBP orally every 8 h for 7 consecutive days, FBP levels in plasma peaked at 182 μg/ml after 45 min [36]. To our knowledge, there is no report on the amount of FBP captured by lung after IP administration in mice, although reports can be found that it can prevent ischemic lung injury in rats [37].…”
Section: Discussionmentioning
confidence: 99%
“…During ischemia/reperfusion in control livers, state 4 increased progressively, while FBP suppressed this increase, although it did not affect state 3. Thus, the RCR of livers preserved with FBP was higher compared to control during ischemia/reperfusion 22 . In this study, mitochondrial parameters related to oxidative phosphorylation, show that the inhibition of electron transport through the respiratory chain in state 3, resulting from hypoxia is observed only in 24 hours of cold ischemia and that FBP was able, as well as the HTK, in maintaining values similar to the control in the 6h period, both for O 2 consumption speed in state 3 and the RCR, thus maintaining the ATP synthesis capacity in that period.…”
Section: Discussionmentioning
confidence: 83%
“…Vexler et al demonstrated the toxicity of FBP in neonatal rats, which receiving 8,000 mg/kg and 27% of those receiving 6,000 mg/kg of FBP intraperitoneally died, because of the chelation of the ionic calcium, creating a reduction in plasmatic ionic calcium, and resulting in convulsions and cardiac fibrillations. Additionally, according to Li et al study , the consumption of FBP by the intestinal epithelium cells could be a major barrier for FBP absorption during oral administration, and a higher dosage may be used when FBP was given orally to achieve the desired clinical therapeutic effect. In our experiment, the administration of FBP in mice is 4 mg/g intraperitoneally, whereas the recommended dose of FBP for patients is 1 g, tid i.v., that is , 42.8 mg/kg per day.…”
Section: Discussionmentioning
confidence: 99%